Determining cyclicity of finite modules. (March 2016) - Lenstra, H.W.; Silverberg, A.
Abstract: We present a deterministic polynomial-time algorithm that determines whether a finite module over a finite commutative ring is cyclic, and if it is, outputs a generator.